PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SEKOLAH DASAR MUHAMMADIYAH 002 ALAM PANJANG - Muhammad Yuzar; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the fact that the learning outcomes of students in science subjects has not been optimal. Based on initial observations that researchers do dikatahui that only 50% or 10 of the total 20 students who received grades above KKM, while 50% or 10 out of 20 students expressed an incomplete or gain value is still below the KKM. This research is a classroom action research conducted in Class IV SD Muhammadiyah 002 Alam Panjang. Research instruments consisted of a Learning Tool used in this research is guided by the Education Unit Level Curriculum (SBC), known as Curriculum 2006 learning device consists of a syllabus, lesson plans, student worksheets and observation sheet. The first meeting of the cycle to the first activity that teachers are only 50% to the category of